ANALISIS TINGKAT KEJENUHAN BANK ISLAM DI INDONESIA - Hapsari, Meri Indri (Journal of Innovation in Business and Economics, 2015)
The research conducted to find out the effect of the number of Islamic bank-ing offices, finance to deposit ratio (FDR), and financing growth to the Is-lamic bank saturation level in Indonesia. The research used panel data analysis with fixed effect model (FEM) as its best estimation model. The re-sult of this research shows that number of Islamic banking offices, Financing Direct Ratio (FDR), and financing growth have a significant effect to the Is-lamic banking saturation simultaneously. Partially, only number of offices has a significant effect, but FDR and financing growth are not significant.Keywords: FDR, Financing Growth , Islamic Bank Saturation, And The Number Of Islamic Banking Offices.